L'Australie interieure : explorations et voyages a travers le continent australien de 1860 a 1862 - Grad, M. A. Charles (Paris : Arthus Bertrand, 1864)
Covers Gregory Expedition (p. 62 - 92), and Dempster and Clarkson Expedition (p. 106-118).
Text in French.
Ferguson, J.A. Bibliography of Australia
Keywords: Settlement and contacts - Explorers; Australia -- Discovery and exploration; Australia, Northern